Financial sector development in transition economies: Lessons from the first decade - John Bonin; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
The first decade of transition witnessed rapid and tumultuous financial sector development.Although, few transition economies have reached the point where institutions and markets fulfill all the functions of market based financial intermediation, progress has been much more rapid than had been anticipated.In many countries, active market-oriented financial institutions function where there was only a state planning mechanism a decade ago. Initial experiences showed that bank privatization programs often failed to achieve independence from government control and from undesirable weak clients.It is now widely accepted that the participation of foreign strategic investors in banking is an effective way of meeting these goals Capital market development is complicated by the need to support the development of institutional infrastructure and regulatory mechanisms while at the same time avoid interfering in the markets.In many instances policy makers expected immature markets and institutions to accomplish unattainable goals.Equity markets cannot be effectively support mass privatization programs.There are still many missing pieces in virtually all of the transition country capital markets.
URN:NBN:fi:bof-201408072046
Keywords: 330; capital markets; financial sector; privatization; transition economies